STUDI BUDAYA MAKAN BAJAMBA PADA ERA MODRENISASI DI KENAGARIAN GADUT KECAMATAN TILATANG KAMANG KABUPATEN AGAM SUMATRA BARAT - Mila Meliza; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research motivated by makan bajamba culture in local society ofKecamatan Tilatang Kamang that is a tradition of Kecamatan Tilatang Kamangcommunity pride. This activity is rich in religious,moral and cultural values. But thisculture have a lot of changes not only in the procedure but also in devotees. Theformulation of the problem in this research is now to makan bajamba now a days inKecamatan Tilatang Kamang society and how sosial care foward makan bajamba inKecamatan Tilatang. The purpose of this research is to know anthusiasm society fowardmakan bajamba culture in Kecamatan Tilatang Kamang society. Data collectiontechniques in this research is observation ,interview and documentation. Respondent ofthis research totaled six people. That is a Datuak,a angku,a bundo kanduang,amandeh,a village child,a young man of Kecamatan Tilatang Kamang. The technicalanalysis in this study use qualitative. The results of this study are change in almostmakan bajamba culture. And also in devotees decreased. There are two factor that isexternal factor andinternal factor. External factor is there other cultural in fluences andinternal factor is new discoveries and as well as insecreasing and decreasingpopilations.Key Words: Makan Bajamba